Critical care in the emergency department: traumatic brain injury. Issue 7 (22nd June 2009) - Mittal, R; Vermani, E; Tweedie, I; Nee, P A
Abstract : Head injury outcome is influenced by the initial insult and the various pathophysiological changes that take place in the posttraumatic phase, some of which may be amenable to intervention. Appropriate measures taken during initial emergency department management and subsequently in the intensive therapy unit can significantly improve outcome. The primary goal is to limit secondary brain injury. Early imaging, rather than admission and observation for neurological deterioration, reduces the time to the detection of life-threatening complications. This paper discusses the current management of severe head injury, some prognostic indicators and methods used to rule out an associated spinal injury.